Relationships between rating of perceived exertion, heart rate and blood lactate during continuous and alternated-intensity cycling exercises - Zinoubi, Badrane; Zbidi, Sana; Vandewalle, Henry; Chamari, Karim; Driss, Tarak (Biology of Sport, 2018)
This study aimed to: i) use Borg’s scale of rating perceived exertion (RPE) in the prescription of cycling training exercises with alternated intensity (S); ii) determine the relationships between RPE and the indices of physiological strains, e.g. heart rate (HR) and blood lactate ([La]), measured during S compared to continuous exercises (C). HR, [La] and RPE were measured in 11 active men at the 5th and 10th minutes of cycling exercises. These exercises were performed with constant or varying intensity corresponding to average power outputs (APO) equal to 160 and 240 W. The protocols with varying intensity consisted of alternated short periods (10 s: S10, or 20 s: S20) of medium and high intensity (120-200 W for APO-160 W and 200-280 W for APO-240 W). During S exercises HR, [La] and RPE were significantly higher compared to C exercises. This effect was more pronounced when the duration of alternated-intensity bouts was longer (S20 versus S10 protocols). The relationships between HR, [La] and RPE (mean or individual data) were not significantly different for the different protocols. However, there was a shift in the relationship between RPE and HR measured at the 5th and 10th minutes of exercise (p<0.001). Moreover, in each protocol, there were significant differences in the individual values of HR or [La] corresponding to the same RPE. The relationships between HR, [La] and RPE were not different between C and S exercises. Individually determined RPE can be used in the prescription of training for both exercises.